(untitled) ("Conference on Universal Science Research 2023", 2023)
This аrticle presents the informаtion аbout metaphor and metonymy is regarded as a tool for promoting linguistics and semiotics. This paper sets out to discuss the types of speech classification of stylistic device, metaphor and metonymy. In doing the discussion, the essay is divided into three sections. The first section provides an introduction with an attempt to provide scholarly definitions of the key terms; the second section gives examples. The final section provides a viable conclusion. The thesis of this paper is that illustrates information about stylistic device.